Tautomerism in 1-hydroxy-2-naphthaldehyde Schiff bases: Calculation of tautomeric isomers using carbon-13 NMR. Issue 4 (2003) - Salman Salman, Salman R. Salman R.; Kamounah Kamounah, Fadhil S. Fadhil S.
Abstract : Tautomeric equilibria in intramolecularly hydrogen bonded Schiff bases is studied on the basis of solution 13 C NMR chemical shifts. NMR spectroscopic data and comparison with two anils model compound, namely, salicylideneaniline (1A) and naphthalylidinequinoline (2A) were used to represent the enol (A) and the keto (H) forms. The 13 C NMR chemical shifts data of the novel series 4A (compounds, 4-12) were used together with the values 13 C chemical shifts data of compounds 1A and 2A to calculate the % keto form. The calculated % keto form of 3A was compared to that calculated for series 4A compounds.